REPRESENTASI STRATIFIKASI MASYARAKAT JAWADALAM NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER - Mardhatillah, Febrianti; Hayati, Yenni (Universitas Negeri Padang, 2019)
This study aims to describe the representation of Javanese social stratificationin Pantai Gadis novel by Paramoedya Ananta Toer, which includes: (1) the formof social stratification of the Javanese community, (2) the causes of of the Javanese community, and (3) the impact of the socialstratification of the Javanese community. This research is a qualitative studyand descriptive methods. Based on the analysis of the data obtained; (1) theform of social stratification in Javanese society is the division of aristocraticgroups (Ndra), priyayi (bureaucrats), and the underprivileged (ordinary people)because they are influenced by factors of power or rank, (2) the causes ofJavanese stratification are several one factor is wealth, power and povertybecause in general the cause is from a person's economic factors, and (3) theimpact of social stratification of the Javanese community one of which isdiscriminatory from various parties both upper and lower classes, then existence of ethnocentrism (boasting of one's own culture ), it means that theculture it has is good and must be numbered while other cultures do not, andthe last one is social conflict, many social conflicts occur because of the 2previous impacts, namely discrimination and ethnocentrism, social conflictsoccur because of inner turmoil towards individuals.Keywords : form of stratification, cause of stratification, and effect ofstratification